The Impact of Information Technology on Coordination: Evidence from the B-2 “Stealth” Bomber - Argyres, Nicholas S. (Organization Science, 1999)
This paper explores the economic processes through which information technology can facilitate coordination within and between firms. The paper presents and analyzes a case study of the B-2 “Stealth” bomber, an aircraft that was designed by four firms almost entirely by computer. The key information systems used in the project were (1) a common-access database to manage part designs and (2) an advanced system to perform structural analysis. These systems played a crucial role in enabling the four firms to coordinate their design and development activities precisely enough to meet the demanding engineering requirements imposed by the aircraft's unique mission. The paper analyses the case study using transaction cost, agency, and information processing theories. The analysis leads to several conclusions about the mechanisms through which the variables emphasized in these theories operated to improve coordination. First, the information systems aided coordination directly by making information processing less costly. Second, this enhanced information processing made the governance of the project more efficient. In particular, by establishing a “technical grammar” for communication, the systems helped to create social conventions around which firms could coordinate their activities, thus limiting the need for a hierarchical authority to promote coordination. This technical grammar also reduced governance costs by reducing asset-specificity, thereby reducing risks associated with contractual holdup. These interactions between communication and governance effects have not been elucidated in the IT/coordination literature. They are important in part because they help explain why the vertically disintegrated organization of the project proved viable. Finally, the systems facilitated decentralized decision-making by reducing agency (measurement) costs. This combination of effects may generalize to other settings in which information technology is used to promote coordination, especially in “virtual” or “disaggregated” corporations.